IMPELMENTASI PROGRAM KAMPUNG KELUARGA BERENCANA DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA BOTOHILITANO KECAMATAN LUAHAGUNDRE MANIAMOLO KABUPATEN NIAS SELATAN - LAIA, NELI ROSMARIYANA; Pasaribu, Jhonson; SINAGA, BUDIMAN NPD (JURNAL ILMIAH SIMANTEK, 2022)
The government in Indonesia is dealing with a serious problem: increasing population growth. Furthermore, the deteriorating Family Planning (KB) program is insufficient to counteract population growth. In this context, alternative efforts or innovations are required, such as a village-level family planning program known as Kampung Keluarga Berencana. This initiative is one of the government's innovations for strengthening the KKBPK program by narrowing the scope of targets to the regional or village level. The site of this study is at Botohilitano Village, Telukdalam Sub-district, South Nias, North Sumatra. The descriptive research method with a qualitative approach was used in this study. The key informants in this study are people who are familiar with the Kampung KB program's implementation, specifically the head of the South Nias P2KBP3A Service and the PLKB of Botohilitano Village. The main informants were two Botohilitano villagers who benefited from the Kampung KB program. One community leader in Botohilitano Village is also a participant in this study. The data was gathered through in-depth interviews and observation techniques. The author then analyzed and explained the data in a qualitative manner. The findings of this study indicate that the implementation of the Kampung KB Program has not been progressing well, as evidenced by the program's termination. Furthermore, there are numerous flaws in various indicators such as resources, inter-organizational relationships, and the implementor's disposition. Suggestions in this study include the need to find a solution by reactivating the Kampung KB program and improving facilities, inter-organizational relations, and the implementor's disposition.